Modulation of gut microbiota by spent coffee grounds attenuates diet‐induced metabolic syndrome in rats. Issue 3 (10th February 2020) - Bhandarkar, Nikhil S.; Mouatt, Peter; Goncalves, Priscila; Thomas, Torsten; Brown, Lindsay; Panchal, Sunil K.
Abstract: Coffee brewing produces spent coffee grounds as waste; few studies have investigated the health benefits of these grounds. This study investigated responses to spent coffee grounds in a diet‐induced rat model of metabolic syndrome. Male Wistar rats aged 8‐9 weeks were fed either corn starch‐rich diet or high‐carbohydrate, high‐fat diet for 16 weeks, which were supplemented with 5% spent coffee grounds during the last 8 weeks. Rats fed non‐supplemented diets were used as controls. High‐carbohydrate, high‐fat diet‐fed rats developed metabolic syndrome including abdominal obesity, impaired glucose tolerance, dyslipidemia, and cardiovascular and liver damage. Body weight, abdominal fat, total body fat mass, systolic blood pressure, and concentrations of plasma triglycerides and non‐esterified fatty acids were reduced by spent coffee grounds along with improved glucose tolerance and structure and function of heart and liver. Spent coffee grounds increased the diversity of the gut microbiota and decreased the ratio of Firmicutes to Bacteroidetes. Changes in gut microbiota correlated with the reduction in obesity and improvement in glucose tolerance and systolic blood pressure. These findings indicate that intervention with spent coffee grounds may be useful for managing obesity and metabolic syndrome by altering the gut microbiota, thus increasing the value of this food waste.